Case Report: Combined transcatheter arterial embolization and aortic stent-graft have better efficacy for bronchial artery aneurysms - Li, Xiangui; Zhang, Haoran; Ma, Wenqi; Lv, Fanzhen; Zhou, Weimin (Frontiers in Cardiovascular Medicine, 2024)
Bronchial artery aneurysm is a rare and fatal condition that requires immediate treatment. However, conventional surgical and transcatheter arterial embolisation treatments are less effective. In the present case, a 76-year-old hypertensive woman was admitted with dizziness and diagnosed with an unruptured bronchial artery aneurysm, which was treated by transcatheter arterial embolisation and aortic stent-graft. The patient's clinical status was stable during the four-year follow-up. Simultaneously, we reviewed 79 papers, analyzing past BAA cases for their etiology, symptoms, and treatment outcomes. We found that catheter arterial embolization and aortic stent-graft implantation, especially for BAA of short-necked and arterial tortuosity, demonstrate superior efficacy compared to other methods. Therefore, we consider this approach to be the preferred choice in clinical BAA treatment.